Association of lower vitamin D levels with inflammation and leucocytes parameters in patients with and without diabetes mellitus undergoing coronary angiography. (20th November 2020) - Verdoia, Monica; Nardin, Matteo; Rolla, Roberta; Negro, Federica; Gioscia, Rocco; Afifeh, Arraa Maddalena Saghir; Viglione, Filippo; Suryapranata, Harry; Marcolongo, Marco; De Luca, Giuseppe; ,
Abstract: Background: Diabetes mellitus has been associated with a chronic low‐grade inflammation and a higher risk of cardiovascular and infectious disease, that could be prevented by the effects of vitamin D. We aimed at evaluating the impact of vitamin D levels on the biomarkers of acute‐phase response, inflammation and glucose metabolism in a large cohort of diabetic patients with cardiovascular disease. Materials and methods: Consecutive patients undergoing coronary angiography were included. Diabetes mellitus was defined as previous diagnosis, specific treatment administration (oral drug or insulin), fasting glycaemia >6.99 mmol/L or HbA1c >48 mmol/L. Glucose parameters, white blood cells, Neutrophil‐to‐Lymphocyte Ratio (NLR), Monocyte‐to‐Lymphocyte Ratio (MLR), C‐reactive protein (CRP) and vitamin D were measured at admission. Vitamin D levels were measured by chemiluminescence immunoassay kit LIAISON® Vitamin D assay (Diasorin Inc). Results: We included 1472 diabetic patients and 2499 non‐diabetic patients that were divided according to vitamin D tertiles. Among diabetic patients, lower levels of vitamin D were associated with female gender ( P = .02), obesity ( P = .004), active smoking and acute presentation ( P < .001) and with a more atherogenic metabolic profile. The levels of white blood cells, leucocytes subfamilies, and inflammatory parameters significantly correlated with vitamin D levels in both patients with and without diabetes (diabetic: P = .012 for WBC, P = .004 for NLR and P < .001 for MLR and C‐reactive protein, non‐diabetic: P < .001 for WBC; NLR, MLR and C‐reactive protein, respectively). Among diabetic patients, results were confirmed at multivariate analysis with no significant interaction according to glycaemic control. Conclusion: The present study demonstrates that, among patients with cardiovascular disease, vitamin D deficiency is associated with metabolic dysregulation and with an elevation of cellular and humoural inflammatory parameters, especially among diabetics, although not being dependent from glycaemic control.